Elf-1 binds to a critical element in a second CD4 enhancer. - Wurster, A L (1994)
The coordinated expression of CD4 and CD8 during T-cell development is tightly coupled with the maturation state of the T cell. Additionally, the mutually exclusive expression of these receptors in mature T cells is representative of the functional T-cell subclasses (CD4+ helper T cells versus CD8+ cytotoxic T cells). We have studied the regulation CD4 gene transcription during T-cell development in an attempt to gain an understanding of the molecular mechanisms involved in T-cell development and differentiation. Here we present the identification of a second transcriptional enhancer in the murine CD4 locus 24 kb upstream of the CD4 promoter. This enhancer is active in mature T cells and is especially active in CD4+ helper T cells. A number of nuclear proteins bind to elements in the minimal CD4 enhancer that includes consensus sites for AP-1, Sp1, Gata, and Ets transcription factor families. We find that the Ets consensus site is crucial for enhancer activity and that the recently identified Ets factor, Elf-1, which is expressed at high levels in T cells and involved in the regulation of several other T-cell-specific genes, is a dominant protein in T-cell nuclear extracts that binds to this site.